(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The topic of (Heritage) and its use has been produced widely in cultural and intellectual aspects, in different temporal stages. It has been produced in architecture in the aspects of conservation, preservation, and rehabilitation of the existing historical or traditional architecture. Then the concept of (Heritage Employment) came in architectural design with the widespread of post-modern thoughts, and the criticism of modernism. And the reactions on modern architecture (International Style) disconnection with historical and traditional values. Research problem is determined as the need to explore and show the concept, and the techniques of architectural heritage employment through historical stages of architectural movements. The research aims to provide knowledge about (Heritage Employment) concept within architecture, besides exploring its employing styles in architectural design. As the research assumes the existence of (Heritage Employment) thoughts and applications in the revival movements of architecture, despite it had not been called with this term until the sixties of the twentieth century. The research explores the historical background of heritage employment since the historical revival of European renaissance, until the contemporary concepts of regionalism and post-modern architecture. In the Arabic region, to present a procedural definition, which shows the different styles of employing the architectural heritage through the historical path of architecture.